Redescription of Hiatella meridionalis d'Orbigny, 1846 (Mollusca, Bivalvia, Hiatellidae) from Argentina - Simone, Luiz Ricardo L.; Penchaszadeh, Pablo E. (Papéis Avulsos de Zoologia, 2008)
The redescription of Hiatella meridionalis (dOrbigny, 1846) is provided as first attempt to improve the systematics of the genus in the regions of Atlantic and western Pacific. This reanalysis is based on specimens collected in the vicinity of the type localities and is based on detailed morphology of samples that some researches consider a single, wide ranging species. From the morphological characters, the more interesting are: a high quantity of papillae at incurrent siphon; the retractor muscles of siphon divided in two bundles; the small size of the palps; the muscular ring in the stomach; and the zigzag fashion of the short intestinal loops. These characters distinguish the species from the other hiatellids so far examined. Type material of the species was examined, by first time illustrated, and the lectotype is designated.